Algicidal activity of Streptomyces sp. LMJ-114 against Microcystis aeruginosa - Du, Mijia; Xie, Qian; Shi, Hongqiu; Yang, Jianyuan; Guo, Qigen; Zhang, Yuqin; Zhang, Binghuo (Frontiers in Microbiology, 2025)
Cyanobacterial blooms have become a worldwide problem. Chemical algicides play important role in controlling cyanobacterial blooms in spite of their potential secondary pollution to aquatic environments. The algicidal microorganisms and their metabolites are potential substitutes for non-selective chemical algicides because of their environmentally friendly characteristics. In this paper, an actinomycete strain, designated as LMJ-114, capable of eliminating cyanobacteria, was isolated from a soil sample collected from Lushan Mountains of China. Strain LMJ-114, belonging to Streptomyces, showed the highest similarity to Streptomyces jiujiangensis JXJ 0074T based on the 16S rRNA gene sequences. This strain showed algicidal activities on both Microcystis and filamentous cyanobacteria. The extracellular water-soluble substances exhibited strong algicidal activity on Microcystis aeruginosa FACHB-905. The algicidal components from strain LMJ-114 could induce M. aeruginosa to produce massive reactive oxygen species (ROS), and seriously affected its antioxidant system. Lipid peroxidation, therefore, occurred seriously in cells of M. aeruginosa, which resulted in 91.6–525.2% higher of malondialdehyde (MDA), and disintegration of gelatinous sheaths, and subsequent sunk cell surface and perforation of the cells. The treatments of both culture broth supernatant and mycelia of strain LMJ-114 significantly affected the contents of retinoic acids (RAs) and microcystins (MCs), and 4 days later, RAs eliminated completely, and 7 days later, microcystin RR (MC-RR) decreased by 96.7 and 87.9%, respectively, and microcystin LR (MC-LR) contents decreased by 89.9 and 81.0%, respectively. L-valine was one of the algicidal compounds in the culture broth supernatant of strain LMJ-114. Strain LMJ-114 and its extracellular metabolites showed potential application in controlling cyanobacterial blooms.